Frontispiece: Molecular Design towards Controlling Charge Transport. Issue 65 (23rd November 2018) - Awais, Mohammad Ahmad; Cai, Zhengxu; Zhang, Na; Yu, Luping
Abstract : The field of single‐molecule electronics today presents innumerable opportunities for basic research in both synthesis as well as physical and theoretical studies. However, such systems are still quite far from actual commercialization of these systems because of a variety of challenges, including charge transport. In their Concept article onpage 17180 ff., L. Yu et al. discuses recent advances on how to control charge transport in single‐molecule systems.